The Comparison of ARMA Estimations in Statistical and Econometric Packages with End-User Implications - Ján, Jan; Quang, Tran Van; Čížek, Ondřej; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2016)
ARMA models rank among the basic methods of the econometric time series analysis and are used for both describing the process and forecasting for a short-term period. The thesis is aimed at a definition and an identification of an ARMA process, a presentation of three estimation methods (the maximum likelihood estimator, the Kalman Filter and ordinary least squares) and, finally, a pursuit of finding the best tool for ARMA modelling. This effort will be based on the fitting the ARMA process in software (Gretl, EViews, STATA and R) using two empirical and one artificial time-series.
Vedoucí práce: Van Quang Tran
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses